Pengaruh Lingkungan Kerja Terhadap Stres Kerja Karyawan PT. Midi Utama Tbk Makassar - Sartina; Kurniawan, Agung Widhi; Musa, Chalid Imran; Dipoatmodjo, Tenri S.P.; Wardhana Haeruddin, Muhammad Ilham (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
The purpose of this study was to determine the effect of the work environment on the work stress of PT. Midi Utama Tbk Makassar, the subjects in this study were employees who worked at PT. Midi Utama Tbk Makassar number 70. This research is included in quantitative research and quantitative analysis to test the research hypothesis using IMB SPSS software version 24.0. The results of this study indicate that the work environment has a positive and significant effect on work stress. This is evidenced by the calculated t value of (4.983) where > t-table (1.99601) and a significance value of 0.000 <0.05